HUBUNGAN PERSONAL HYGIENE DAN SANITASI LINGKUNGAN DENGAN KEJADIAN SKABIES DI WILAYAH KERJA PUSKESMAS SALAWU KABUPATEN TASIKMALAYA - Nisa Asyari; Andik Setiyono; Yuldan Faturrahman (Jurnal Kesehatan Komunitas Indonesia, 2023)
Scabies is a skin disease where this disease is included in the environment-based disease. In Indonesia, scabies is commonly referred to as scabies or budukan. Scabies is a skin disease caused by parasites. Scabies is caused by mites or tiny ticks of the species Sarcoptes scabiei hominis. Factors that contribute to the spread of scabies include an unhealthy environment, limited clean water, and poor personal hygiene. This study aims to determine the relationship between personal hygiene and environmental sanitation with the incidence of scabies in the work area of the Salawu Health Center. This study uses a case control design. Data analysis in this study used the chi square test with a total sample of 144 including 48 case samples and 96 control samples. The results showed that there was a significant relationship between personal hygiene, namely skin hygiene, hand, foot and nail hygiene, hair hygiene, and genital hygiene with a value (p=0.000) and the incidence of scabies. The results showed that there was a relationship between ventilation (p=0.003), lighting (p=0.001), and the physical quality of clean water (p=0.002) with the incidence of scabies. Advised to people maintain good personal hygiene and maintain environmental sanitation. For health service workers, it is hoped that they can provide counseling to the surrounding community regarding material regarding scabies and how to prevent it.